THE INFLUENCE OF GENOMICS ON PERSONALIZED MEDICINE AND PUBLIC HEALTH POLICIES - Dr Ashwini L H; Dr Vinaykumar L H; Dr Hanumanaik L (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
With genomics, precise healthcare interventions resulting from genetic profiles enable revolutionizing personalized medicine as well as public health policy. This study explores how genomic data can affect healthcare by examining the associations between genetic variants and major health conditions such as cardiovascular disease, type 2 diabetes, and lung cancer. Using a mixed methods approach, the study combines a systematic review of existing literature, analysis of data from reputable genomic databases, and case studies to ground genomics in healthcare. Population Specific Genetic Markers were identified using Genome Wide Association Studies (GWAS) and Polygenic Risk Scores (PRS) and significant associations were found that highlight the predictive power of genomics in the prevention and treatment of disease. Results show that increased likelihood of policy adoption is associated with high PRS values, implying that genomic insights can be used to target public health interventions. Specifically, ethical considerations of data privacy, patient consent and equitable access were considered as genomics was integrated into public health methods, with the call to integrate responsibly. The present study provides novel insights by linking PRS to the adoption of public health policy and demonstrating the potential for genomics to facilitate both personalized healthcare and equitable public health policy. Future research should be directed to expanding genetic databases regarding populations which can be underrepresented and refining algorithms that incorporate lifestyle factors to improve predictive accuracy.